2020
DOI: 10.3892/or.2020.7471
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of GPSM2 is associated with primary resistance to paclitaxel in breast cancer

Abstract: Paclitaxel is one of the most effective chemotherapy drugs for breast cancer worldwide but 20-30% patients show primary resistance to the drug. Screening and identification of markers that facilitate effective and rapid prediction of sensitivity to paclitaxel is therefore an urgent medical requirement. In the present study, G protein signaling modulator 2 (GPSM2) mRNA levels were significantly associated with taxane sensitivity in experiments based on the Gene Expression Omnibus (GEO) online database. Immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Subsequent studies confirmed this finding and also found that its nuclear expression is significantly linked to worse prognosis [11]. Interestingly, Zhang et al demonstrated that GPSM2 is down-regulated in paclitaxel-resistant samples of breast cancer patients and could be a drug-resistance gene in breast cancer [10]. Consistent with previous research, we also found that the expression level of GPSM2 in breast cancer tissues increased significantly when compared to normal samples from Oncomine and UALCAN analysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Subsequent studies confirmed this finding and also found that its nuclear expression is significantly linked to worse prognosis [11]. Interestingly, Zhang et al demonstrated that GPSM2 is down-regulated in paclitaxel-resistant samples of breast cancer patients and could be a drug-resistance gene in breast cancer [10]. Consistent with previous research, we also found that the expression level of GPSM2 in breast cancer tissues increased significantly when compared to normal samples from Oncomine and UALCAN analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Fukukawa et al showed that GPSM2 is overexpressed in breast cancer tissues [8], while Deng et al stated that its nuclear expression is an unfavorable prognostic indicator [9]. Furthermore, bioinformatics analysis and in vivo verification have suggested that GPSM2 negatively influenced patient response to paclitaxel, one of the most effective and well-tolerated chemotherapy drugs for breast cancer [10]. Meanwhile, members of the GPSM family are known to be associated with other neoplasms, namely lung [11], prostate [12], and pancreatic cancer [13].…”
Section: Introductionmentioning
confidence: 99%
“…The 9-gene model included: LAMA3, LGALS1, SGCG, VEGFA, WNT5A, MATN3, ANPEP, FUCA1, and FLNA. LAMA3 encodes a laminin and has been shown to be closely related to the prognosis of patients with ovarian cancer 21 and pancreatic cancer. 22 LGALS1 is a widely studied galectin, and a large number of studies have confirmed that it is closely associated with the prognosis of various solid tumor patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both stathmin and G Protein Signaling Modulator 2 (GPSM2/LGN) regulate the mitotic spindle and the G2-M phase of the cell cycle [ 75 , 90 , 91 , 92 ]. Consequently, alterations in stathmin or GPSM2/LGN could lead to impaired mitotic spindle function and taxane resistance [ 75 , 93 ]. The knockdown of GPSM2 increases the resistance of BC cells to PTX both in vitro and in vivo [ 93 ].…”
Section: Taxane Resistance In Breast Cancermentioning
confidence: 99%
“…Consequently, alterations in stathmin or GPSM2/LGN could lead to impaired mitotic spindle function and taxane resistance [ 75 , 93 ]. The knockdown of GPSM2 increases the resistance of BC cells to PTX both in vitro and in vivo [ 93 ]. Phosphorylation prevents stathmin from binding to tubulin, effectively controlling stathmin’s ability to impact MT stabilization [ 94 ].…”
Section: Taxane Resistance In Breast Cancermentioning
confidence: 99%